Social ideological influences on reported food consumption and BMI - Worsley Anthony; Wang Wei C; Cunningham Everarda G (BMC, 2008)
Abstract Background The purpose of this study was to investigate relationships between ideological beliefs, perceptions of the importance of health behaviours, health attitudes, food consumption, and Body Mass Index (BMI). A behavioural model was hypothesized based on the Theory of Reasoned Action (Fishbein & Ajzen, 1975). Methods A survey was conducted among shoppers aged between 40 and 70 years at Eastland Shopping Centre, Melbourne, Australia. The hypothesized model was tested with this empirical data (n = 410) for younger (n = 151) and older (n = 259) age groups using structural equation modelling. Results The findings generally support the study hypotheses. For both groups, egalitarianism had a direct and positive influence on perceptions of the importance of health behaviours. Materialism and masculinity impacted negatively on health attitudes, which positively influenced importance of health behaviours. Perceptions of importance of health behaviours impacted positively on the consumption of healthy foods such as vegetables and fruits, but negatively on consumption of unhealthy foods including sweets and fats. However, BMI was significantly influenced by the consumption of unhealthy foods (e.g., sugar and fats) only for the younger age group. Hence, the associations between beliefs, attitudes, consumption behaviours, and BMI outcomes differed between younger and older age populations. Conclusion Social ideological beliefs appear to influence health attitudes and thereafter, the consumption of healthy and unhealthy foods and BMI via different pathways.